Bordered penality in the Netherlands: The experiences of foreign national prisoners and prison officers in a crimmigration prison. (December 2020) - Brouwer, Jelmer
In recent years there has been growing attention for so-called crimmigration prisons: all-foreign prisons with immigration staff embedded where not rehabilitation, but deportation is the ultimate aim. Following Norway and the United Kingdom, since 2014 the Netherlands is another country with such a prison. This article analyses penal policies in the Netherlands vis-à-vis foreign national prisoners, including the establishment of the crimmigration prison. Drawing on extensive empirical fieldwork in the crimmigration prison, it subsequently examines how this is experienced and understood by both prison officers and foreign national officers. The results show that the limited opportunities to work on rehabilitation means that prison officers struggle to find meaning and satisfaction in their work. For prisoners, experiences in the crimmigration prison strongly depend on their subjective identity and attachment to the Netherlands. Whereas the lack of meaningful activities and remote location of the prison considerably add to the pains they experience, specific elements of the prison also help to mitigate some of the pains foreign national prisoners most commonly experience, especially isolation and uncertainty. The article finishes by a discussion about what this says about how the state should treat individuals it seeks to both punish and deport.